U.S. Wage-Inequality Trends and Recent Immigration - Lerman, Robert I (American Economic Review, 1999)
How should we assess the changing economic status of workers and families in the United States? The answer is obvious to many, including outstanding economists who decry the meager wage growth and rising wage and income inequality in the United States since 1979 (Paul Krugman, 1992; Richard Freeman, 1996/1997; James Tobin, 1996/1997 ) . According to Freeman (1996/1997) the following ‘‘facts are not in dispute’’: